Growth performance of FH male calves fed milk replacer made of local ingredients for veal production - Wina, Elizabeth; Mathius, I-Wayan; Tangendjaja, Budi (Indonesian Journal of Animal and Veterinary Sciences, 1996)
The research was designed to evaluate the local feedstuff to be used in milk replacer (MP) and its utilization for veal production . Fifteen male calves of the Friesian Holstein breed, 5-6 weeks old were used in the experiment lasting for 8 weeks. The treatments were (i) commercial milk replacer (SPK), (ii) local (SPL-1) and (iii) mixture ofSPK and SPL-1 (SPKL). The amount of dry matter offerred is 3 % of live weight each and was given twice daily (in the morning and late afternoon) . Elephant grass (0 .5 kg) was offerred at noon . The observed parameters were average daily gain (ADG), dry matter (DM) and crude protein (CP) intake, carcass percentage, weight of carcass components, physical and chemical characteristics of meat. The results show that feed consumptions were 1,981, 1,613 and 1,050 g1day and ADGs were 897,496 and 73 g for treatments SPK, SPKL and SPL, respectively . Carcass percentage was 56.84 and 58 .76% with protein content was 87 .47 and 84 .78% for treatments Â SPK and SPKL, respectively . The benefit per head of calf was higher when fed mixture of local and commercial MP than fed only commercial MP but the benefit per day was higher when fed commercial MP than mixture of local and commercial. In conclusion, a cheaper milk replacer with less milk protein content resulting in a lower gain but higher benefit per head of calf than a commercial milk replacer containing high milk protein content Â  Key words : veal, male calves, milk replacer